Perianal Tuberculosis in an Immunocompetent Patient: Exploring the Uncommon Manifestation - Ferreira, Ana Rita; Pereira, Hugo; Castro, Bárbara; Ferreira, Joana; Esteves, Joana; Pereira, Bela; Vale, Sílvio; Oliveira, Manuel (Journal of Coloproctology, 2024)
As it is an infrequent etiology, the diagnosis of perianal tuberculosis is challenging, especially in the absence of a pulmonary focus. TB should be considered in the differential diagnosis of perianal ulcers, fistulas, abscesses, mainly in non-healing and recurrent anal lesions. Treatment with anti-TB agents can provide complete recovery. Furthermore, these lesions are often diagnosed later after complete histopathological and mycobacterial results, where the benefit of avoiding morbid multiple surgeries by effective anti-TB treatment is lost.We reported a rare case of an immuno-competent patient with perianal TB, which was the first manifestation of the disease. A fit-and-well man in his 20s presented a large perianal abscess. Unexpectedly, his chest X-ray showed a rounded hyper-transparency in the left lung. The abscess was drained. Posterior investigation with culture analysis from pus swabs and sputum revealed the presence of Mycobacterium tuberculosis complex infection. After completing the 6 months of oral administration of anti-TB drugs, the patient was asymptomatic.By highlighting this unusual manifestation, we aim to improve clinicians' awareness of perianal TB, facilitating early recognition and appropriate management.
Keywords: extrapulmonary tuberculosis; mycobacterium tuberculosis complex infection; perianal tuberculosis; inflammatory bowel disease; tuberculosis-associated immunocompetent patient